Peran Orangtua Menyikapi Pornografi Pada Remaja Melalui Komunikasi Efektif - Djudjur Luciana Radjagukguk; Yayu Sriwartini (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The development of the internet has penetrated into all lines of modern life, but not all have a positive effect. One of the negative effects of internet development is pornography, indirectly these effects have an impact on children. In fact, this is the opening door for many crimes, one of which is child sexual crime in the online realm. The resulting impact of pornography on children requires the role of parents to prevent children from being exposed to pornography so that they do not become addicted or at least be able to recognize the characteristics of children who are addicted to pornography. This happens most easily in children who store boredom, loneliness, fear, anger, and stress. The role of parents becomes greater in supervising children to pay more attention to everything that children do both inside and outside the home, especially the use of advanced technology, such as the internet. So an approach is needed through effective communication. Parents must take the initiative to build effective communication.